The Use Of Mini-Games In Chess Education - Ricardo Gregorio Castor Corpuz III; Luisa Corpuz M.; Sheemal Shareeka; Asmita Sharma; Samuela Korovou; Narayan, Aayush; Ravitesh Prasad; Narko Abraham Kabolo (Զանգակ հրատ.)
This study examines the effect of integrating minigames into chess training on the interest and engagement of new players compared to traditional teaching methods. The results show that the enthusiasm of most new players increased significantly when exposed to the minigames. The experimental group that used the curriculum enriched with minigames showed substantially higher interest than the control group that received regular instruction. Current research supports these findings by highlighting the exciting nature of minigames, making learning more playful and exploratory. Minigames provide a structured yet accessible way to break down the complexity of chess, improve motivation, and promote a positive attitude toward learning. The novelty and variety of minigames encourage continued interest and engagement, potentially reinvigorating chess education and fostering engagement in the chess community. Research of long-term effects on different populations and individual learning preferences is warranted to fully understand the potential of minigames to improve chess training.
Keywords: Education